Impact of obesity on echocardiographic parameters and N-terminal pro-brain natriuretic peptide levels in patients with heart failure with mid-range ejection fraction: unanswered questions - E. A. Lyasnikova; A. A. Kuular; A. V. Pavlovskaya; A. N. Vlasenko; A. V. Kozlenok; A. Yu. Babenko; M. Yu. Sitnikova; E. V. Shlyakhto (Российский кардиологический журнал)
Aim. To analyze and compare the clinical, echocardiographic characteristics and serum N-terminal pro-brain natriuretic peptide (NT-proBNP) levels depending on the central cardiometabolic risk factors, with a focus on obesity, in patients with heart failure (HF) with mid-range ejection fraction (HFmrEF).Material and methods. The study included 111 patients with old myocardial infarction and HFmrEF (men, 100%; mean age, 60 years) predominantly of NYHA class II. Echocardiography and blood sampling for NT-proBNP were performed with sinus rhythm. Left atrial volume (LAV) and left ventricular mass (LVM) were indexed to body surface area (BSA) and height raised to a power.Results. Type 2 diabetes, overweight and obesity were diagnosed in 25%, 19%, 38% of cases, respectively, and were associated with greater changes in the morphologic and functional left ventricular parameters. There were no intergroup differences among patients with and without obesity in the LAV and LVM indexed to BSA. However, in patients with a body mass index (BMI) ≥30 kg/m2, the LAV indexed to height squared and LVM indexed to height2,7 were higher (p<0,05 for all). In 11% of obese patients, there were no changes in the criterion LAV or LVM values indexed to BSA, but the values indexed to height raised to a power exceeded the standard values. In 20% of patients with clinical manifestations of stable HFmrEF and structural and functional echocardiographic criteria, NT-proBNP were ≤125 pg/ml. An inverse correlation was found between NT-proBNP and BMI (r=-0,29; p=0,008), and lower values of myocardial stress marker were observed in obese patients (p=0,048).Conclusion. Considering the high incidence of obesity in patients with HFmrEF and its ability to reduce NT-proBNP, an algorithm modification is required for diagnosing HFmrEF as follows: focus on clinical and personalized echocardiography data, taking into account the obesity and, possibly, indexing the threshold natriuretic peptide values in patients with BMI ≥30 kg/m2. The issues of indexation of echocardiographic parameters depending on morphometric parameters in obese patients today remain open, predetermining the limitations in diagnosis of heart failure with left ventricular ejection fraction >40%. This requires the search for optimal standardization and the development of a unified methodological approach.